Factors influencing growth of mature sycamore trees (Acer pseudoplatanus L.) on carbonate bedrock - Kadunc, Aleš (Zbornik gozdarstva in lesarstva, 2005)
This paper presents the growth potential of sycamore (Acer pseudoplatanus L.) on four types of forest sites located on carbonate bedrock. The research covers sycamore sites (Aceri-Fraxinetum ill.), beech sites (Lamio orvalae-Fagetum), beech sites planted with Norway spruce, and silver fir-beechsites (Omphalodo-Fagetum aceretosum). The analyses for each forest type were carried out on five plots. Our aim was to determine the effect of site factors and stand parameters on sycamore growth. Site productivity (SP) is positively correlated with soil depth, coarse silt percentage in the cambichorizon, the content of phosphorus in leaves and, partly, with potassium. The effect of nitrogen supply on height growth or SP was not confirmed. Furthermore, height growth on sites with a higher rate of nutrient cycling, higher macronutrient supply and higher sand percentage in the cambic horizon is significantly faster. As to the growth of basal area, in addition to positive dependences of crown size, many other correlations with site factors were confirmed.
Keywords: Acer pseudoplatanus L.; javor; rastiščni dejavniki; sestoji